Developing of Rainfall Intensity-Duration-Frequency Model for Sulaimani City - Hamaamin, Yaseen Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2017)
The intensity-duration-frequency (IDF) relationships are crucial for water resources planning, management and design of hydraulic structures. Sulaimani City is one of the largest cities in Iraq, needs special stormwater management due to rapid development in land use. In this study IDF curves were generated from daily rainfall data for different rainfall durations (10, 20, 30, 60, 120, 360, 720, 1440 minutes) with returning frequencies of (2, 5, 10, 25, 50, 100 years), to predict rainfall intensity in different durations and return frequencies for Sulaimani City. Furthermore, an average empirical formula was developed, to be used as a general equation to predict the rainfall intensity at any duration and returning period straightforwardly. Results of the study showed a good match between the rainfall intensities using the general empirical formula compared to the IDF curves with excellent coefficient of determination (R2=1) between results from the empirical formula and the IDF curves. Also performance of the empirical equation was confirmed through a chi-square test between rainfall intensity values for both the IDF curves and the empirical equation.
Keywords: IDF relationships; Rainfall intensity; Rainfall duration; Rainfall frequency; Sulaimani city